Comparison of Lingual Mucosa and Buccal Mucosa Grafts used in Inlay Urethroplasty in Failed Hypospadias of Pre-Pubertal Boys in a Khyber Teaching Hospital - Hazratullah, Amir Taimur Khan, Hamza Khan Shahbazi, Syed Muhammad Haider, Moath Ahmad Abdullah Almuradi, Muhammad Aness Iqbal, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: The surgical approach toward hypospadias repair in pre-pubertal boys with several unsuccessful surgeries is extremely difficult because of tissue loss and possibility of tissue complications. While buccal mucosa grafts (BMGs) remain the most widely used approach, there has been recent interest in lingual mucosa grafts (LMGs) which seem to offer potential benefits in terms of donor site morbidity and graft availability. At Khyber Teaching Hospital, Peshawar, this study assesses and compares BMG and LMG outcomes in inlay urethroplasty for complex hypospadias patients' cases. Methods: A retrospective analysis study of 62 pre-pubertal boys was done from July 2022 to July 2023. Patients had at least two failed hypospadias repairs. The patients’ records were reviewed and the study group was separated into BMG (n=29) and LMG (n=33) subgroups. Primary outcome measures were surgical success defined as a functional urethra after surgical intervention and complication rates for fistula, stricture, ventral curvature, aid, and peak flow during uroflowmetry. Cosmetic evaluation was performed with validated “How was it? (HOSE)” scores. Statistical was done with SPSS 18.0 for statistical chi square/t-tests and was considered significant if P value was <0.05. Results: Both groups had comparable complication rates (BMG: 83.0%, LMG: 84.8%) and success rates (BMG: 17.0%, LMG: 15.0%). There were no statistically relevant differences for fistula (6.8% and 6.0%), stricture (6.8% and 3.0%), or ventral curvature (3.4% and 6.0%) rates (p>0.05). The mean peak flow and HOSE score for patient’s (BMG: 14.28±1.03, LMG: 14.34±0.95) were comparable. Compared with BMG, LMG harvesting had less complications at the donor site. Conclusion: Both LMG and BMG deliver the same results for unsuccessful hypospadias repair in boys who have not reached puberty. However, LMG may be used when buccal tissue is not available, or there are unsuccessful attempts to harvest it. This adds to the literature suggesting LMG is a dependable method for advanced pediatric urethroplasty and increases the possibilities for repair in places with few resources. Keywords: Lingual mucosa, buccal mucosa, graft complications, hypospadias, urethroplasty.